Kesesuaian Dosis Vankomisin pada Pasien Penyakit Ginjal Kronik Stadium 3 dan 4 di Bangsal Penyakit Dalam RSUP Dr. M. Djamil Padang - Muslim Suardi; Marissa Sofjan; Raveinal Raveinal (Fakultas Farmasi Universitas Andalas, 2016)
Vancomycin is a glycopeptide antibiotic which almost completely eliminated by renal unchanged in the urine (> 90%). Elimination of vancomycin is delayed in patients with renal insufficiency. The purposes of the research were to examine dosing adjustment and quantity individualized dose of vancomycin in patients with chronic kidney disease in Internal Ward of Dr. M. Djamil Padang Hospital based on pharmacokinetics dosing method. The study was designed by observational retrospective method conducted on patient’s medical record during January 2015 – March 2016. A number of 21 patients were treated using vancomycin with chronic kidney disease stage 3 and 4. Results showed that 19.05% patients received exceed dose based on pharmacokinetic dosing method calculation. Clearance of vancomycin in patients with chronic kidney disease on stage of 3 and 4 were 1.88 ± 0.28 and 0.88 ± 0.21L/h, respectively. The elimination half-life prolonged to patients with chronic kidney disease stage 3 and 4 were 14.11 ± 2.89 and 24.48 ± 5.44, respectively. While accumulation factor in patients with chronic kidney disease on stage of 3 and 4 were 0.50 ± 0.1 and 0.67 ± 0.09, respectively.